Udostępniania informacji publicznej w Biuletynie Informacji Publicznej a ochrona prywatności osób fizycznych - Miłosz, Michał (Kwartalnik Prawa Publicznego, 2012)
The article deals with legal aspects concerning the problem of infringement of privacy connected to publishing of information by public authorities at the Internet sites at the official Bulletin of Public Information. In the text the legal framework for the publishing of public information in the Bulletin of Public Information is presented. Different kinds of public information that has to be or might be published on-line based on the provisions of the Polish act of 6.9.2001 on access to public information are pointed out in the text. Protection of the privacy of natural persons is indicated as one of the important legal exceptions restricting the access to public information. This exception fully applies also to publishing of information at sites of the Bulletin of Public Information. The application of this exception, as well as the rules of conduct that have to be applied by public authorities to publication of information including personal data are discussed. The legal bases of the administrative control (conducted by the General Inspector of Personal Data Protection) and the court control in the cases of unlawful publishing of personal data in the Bulletin of Public Information are analyzed in this study. Some administrative decision and court judgments concerning the problem are presented. The author stresses that privacy issues have to be taken into particular consideration by the public authorities when they publish public information on the Internet sites of the Bulletin of Public Information.